IL-24 Promotes Apoptosis through cAMP-Dependent PKA Pathways in Human Breast Cancer Cells - Persaud, Leah (Int J Mol Sci, 2018)
Interleukin 24 (IL-24) is a tumor-suppressing protein, which inhibits angiogenesis and induces cancer cell-specific apoptosis. We have shown that IL-24 regulates apoptosis through phosphorylated eukaryotic initiation factor 2 alpha (eIF2α) during endoplasmic reticulum (ER) stress in cancer. Although multiple stresses converge on eIF2α phosphorylation, the cellular outcome is not always the same. In particular, ER stress-induced apoptosis is primarily regulated through the extent of eIF2α phosphorylation and activating transcription factor 4 (ATF4) action. Our studies show for the first time that cyclic adenosine monophosphate (cAMP)-dependent protein kinase A (PKA) activation is required for IL-24-induced cell death in a variety of breast cancer cell lines and this event increases ATF4 activity. We demonstrate an undocumented role for PKA in regulating IL-24-induced cell death, whereby PKA stimulates phosphorylation of p38 mitogen-activated protein kinase and upregulates extrinsic apoptotic factors of the Fas/FasL signaling pathway and death receptor 4 expression. We also demonstrate that phosphorylation and nuclear import of tumor suppressor TP53 occurs downstream of IL-24-mediated PKA activation. These discoveries provide the first mechanistic insights into the function of PKA as a key regulator of the extrinsic pathway, ER stress, and TP53 activation triggered by IL-24.